Tuning of the crystal engineering and photoelectrochemical properties of crystalline tungsten oxide for optoelectronic device applications. Issue 32 (28th August 2015) - Zheng, Jin You; Haider, Zeeshan; Van, Thanh Khue; Pawar, Amol Uttam; Kang, Myung Jong; Kim, Chang Woo; Kang, Young Soo
<x xml:space="preserve">Abstract</x> WO3 crystals with {002} or {111} facets primarily exposed, WO3 films with dominant orientations, doping and heterostructuring are highlighted.